A Better Approach of Assessing Lalerality by Using Combined Foot and Eye Dominance Scale in Mentally Healthy Subjects - Akabalieva K.; Kotetarov V.; Beshkov A. (Acta Medica Bulgarica, 2023)
To investigate the reliability (internal consistency) of a Combined Foot and Eye Dominance Scale in healthy subjects.